2001
DOI: 10.1139/v01-079
|View full text |Cite
|
Sign up to set email alerts
|

Transition metal phthalocyanine and porphyrin complexes as catalysts for the polymerization of alkenes

Abstract: Vanadium phthalocyanine and porphyrin complexes, in conjunction with methylaluminoxane (MAO) or EtAlCl2 cocatalyst, have been found to catalyze the homopolymerization of ethene. In addition, the copolymerization of ethene with propene and 1-decene was achieved with the vanadium phthalocyanine complex and MAO. Nickel phthalocyanine complex was also found to catalyze the polymerization of ethene in the presence of MAO. However, only dimerization was observed when EtAlCl2 was used as the cocatalyst.Key words: pht… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 2 publications
0
10
0
Order By: Relevance
“…55−58 For example, it has been reported that soluble vanadyl and nickel naphthalocyanines can polymerize ethene at high pressure. 59 Because of the cis arrangement of the chlorido ligands, 5 seemed a suitable precatalyst for olefin polymerization (Scheme 8). We therefore tested the activity of dichlorido compound 5 and titanyl Pc 1 in the polymerization of ethene at atmospheric pressure using 1000 equiv of MAO as cocatalyst.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…55−58 For example, it has been reported that soluble vanadyl and nickel naphthalocyanines can polymerize ethene at high pressure. 59 Because of the cis arrangement of the chlorido ligands, 5 seemed a suitable precatalyst for olefin polymerization (Scheme 8). We therefore tested the activity of dichlorido compound 5 and titanyl Pc 1 in the polymerization of ethene at atmospheric pressure using 1000 equiv of MAO as cocatalyst.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…76 A study of the reactions of Ta-alkyl bonds to insert small molecules including CO 2 and isocyanide affords insertion products such as the η 2 -iminoacyl-η 1 -carbamate complex [TaCp*(NBu t )(η 2 -CMe᎐ ᎐ NAr)(η 1 -O 2 C(NMe 2 )]12. 77 Complexes studied that are reported to catalyse alkene polymerisation include vanadium phthalocyanine complexes (after alkylation with AlEtCl 2 ), 78 and vanadium-() and -() complexes with O,N-chelating aminophenolate ligands. 79 The alkene ligand in the Nb derivative [{Nb(silox) 3 } 2 (η 1,2 -η 5,6 -C 8 H 8 )] (silox = Bu t 3 SiO) undergoes an alkene-to-alkylidene rearrangement upon dehydrogenation.…”
Section: Vanadium Niobium and Tantalummentioning
confidence: 99%
“…7 Vanadium phthalocyanines have applied in photoelectrophoretic and optical recording materials 8 and have been also used for polymerisation of ethylene in the presence of methylaluminoxane (MAO) as a co-catalyst. 9 Therefore, immobilization of the metal phthalocyanine via covalent attachment to the nano magnetic core-shell is an interesting approach to facilitate catalyst recovery, recycling, and to reduce effluent contamination. In addition, these immobilized catalysts resistant to leaching due to the chemical bonding between the support and the metal phthalocyanine.…”
Section: Introductionmentioning
confidence: 99%